2015
DOI: 10.5301/ejo.5000700
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Depression Prevalence in Patients with Stargardt Disease using PHQ-9 and Zung Scores

Abstract: Patients with Stargardt disease exhibited more depressive symptoms compared to healthy individuals according mainly to PHQ-9 scores. Moderate depression was significantly correlated visual function decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
3
9
1
Order By: Relevance
“…Depressive symptoms were determined based on participant's responses to the PHQ-9 questionnaire in the NHANES 2011–2012 cycle. PHQ-9 is the 9-item self-report depression scale that asks questions about the frequency of symptoms of depression over the past 2 weeks ( Kroenke et al, 2001 , Moschos et al, 2016 ). Each item can be scored from 0 (not at all) to 3 (nearly every day) ( Kroenke et al, 2001 ).…”
Section: Methodsmentioning
confidence: 99%
“…Depressive symptoms were determined based on participant's responses to the PHQ-9 questionnaire in the NHANES 2011–2012 cycle. PHQ-9 is the 9-item self-report depression scale that asks questions about the frequency of symptoms of depression over the past 2 weeks ( Kroenke et al, 2001 , Moschos et al, 2016 ). Each item can be scored from 0 (not at all) to 3 (nearly every day) ( Kroenke et al, 2001 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have evaluated the aforementioned association, detecting depression in patients with age-related macular degeneration [ 25 ], glaucoma [ 28 ], retinitis pigmentosa [ 29 ], and Stargardt disease [ 30 ]. As for the KC, studies demonstrated controversial conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…The raw score converted to a 100-point scale is the SDS/SD Index. The classifications according to the final SDS Index are as follows: those below 49 are considered normal, those between 50 and 59 are considered to have mild depression, 60–69 to have moderate or marked depression, and those who score 70 and above are considered to have severe depression 3539. All subjects completed the questionnaires twice, before and after stimulation.…”
Section: Methodsmentioning
confidence: 99%